2020
DOI: 10.47102/annals-acadmedsg.2020242
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Audit of Airway Code Activations and Adverse Events in Two Tertiary Hospitals

Abstract: Introduction: Airway management outside the operating room can be challenging, with an increased risk of difficult intubation, failed intubation and complications. We aim to examine airway practices, incidence of difficult airway and complications associated with airway code (AC) activation. Methods:We conducted a prospective audit of AC activations and adverse events in two tertiary hospitals in Singapore. We included all adult patients outside the operating room who underwent emergency intubation by the AC t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 29 publications
4
10
1
Order By: Relevance
“…In contrast to other studies, 10 11 the AC teams were activated more frequently outside working hours than during working hours in our study, which may be attributed to a lack of supervising staff in the wards and ICU on weekends, holidays, and nights. Because emergency intubation performed by primary physicians outside of working hours is associated with a lower success rate and higher complication rate compared to that performed during working hours, 12 13 it is highly recommended that the AC team provides continuous coverage.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to other studies, 10 11 the AC teams were activated more frequently outside working hours than during working hours in our study, which may be attributed to a lack of supervising staff in the wards and ICU on weekends, holidays, and nights. Because emergency intubation performed by primary physicians outside of working hours is associated with a lower success rate and higher complication rate compared to that performed during working hours, 12 13 it is highly recommended that the AC team provides continuous coverage.…”
Section: Discussioncontrasting
confidence: 99%
“…Most studies have recommended a multidisciplinary model of the airway rapid response team outside of the operating room, including an anesthesiologist, ENT physician, emergency department physician or trauma surgeon, nurse, pharmacist, and respiratory therapist. 5 6 7 8 9 10 11 If effective teamwork, communication, and coordination are ensured among clinicians, an ENT physician can manage tracheostomy-related problems and create surgical airways. However, instead of including the ENT physician in all AC activations, we implemented a separate ENT airway call system, similar to a previous study.…”
Section: Discussionmentioning
confidence: 99%
“…[18,19] The respiratory cause was one of the most common causes of emergency intubation, with the internal medicine ward being the most common code activation site, which is consistent with the results of previous reports. [10,[14][15][16]20] This study demonstrated that the frequency of Code D-delta activation was equal during and outside office hours, similar to the results of other reports from tertiary care hospitals. [13,16,20] The Code D-delta team successfully handled 85% of intubations at the activation scene, whereas 10% (two cases) were appropriately reevaluated and transferred to the OR for flexible bronchoscope-assisted intubation by the otolaryngology resident and anesthesia staff.…”
Section: Discussionsupporting
confidence: 89%
“…[9][10][11] In some centers, the emergency airway response team is assigned to improve airway quality and reduce the associated risks and complications. [13][14][15][16] The members of the emergency airway team vary among centers and usually include multidisciplinary personnel, such as an anesthesiologist, otolaryngologist, emergency medicine physician, trauma surgeon, and risk managers. [13,15,16] Some studies have reported that the airway call team consists of an anesthesiologist and senior anesthesia resident.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation